Analisis Literatur Penggunaan Model Rasch untuk Validasi Instrumen Asesmen Pendidikan : Tren, Temuan, dan Implikasi - Neva Lionitha Ibrahim (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to examine the use of the Rasch Model in the validation of educational assessment instruments through the literature review study method. A total of 20 scientific articles published in the last five years were analyzed to examine the application of the Rasch Model in evaluating the validity, reliability, and quality of the question items. The results of the study show that the Rasch Model is consistently used in the development of instruments that objectively measure students' abilities, attitudes, and character. This model allows for a detailed analysis of the characteristics of the item and the respondent, as well as supporting the development of more accurate and fair instruments. Recent trends show the integration of the Rasch Model with digital technologies and statistical analysis software such as Winsteps, R, and ConQuest, which strengthens the data analysis process. The study concludes that the Rasch Model makes a significant contribution to improving the quality of learning evaluation and is very relevant to be applied more widely at various levels of education, especially in order to support data-based and objective measurement-oriented assessments.